Addressing an Unfulfilled Expectation: Teaching Students With Disabilities to Write Scientific Arguments. (April 2023) - De La Paz, Susan; Levin, Daniel M.; Butler, Cameron
Students with disabilities (SWD) in general education science classes are expected to engage in the scientific practices and potentially in the writing of arguments drawn from evidence. Currently, however, there are few research-based instructional approaches for teaching argument writing for these students. The present article responds to this need through the application of an instructional model that promises to improve the ability of SWDs to write scientific arguments. We approach this work in multiple ways. First, we clarify our target group, students with high incidence disabilities (learning disability, ADHD, and students with speech and language impairments), and discuss common cognitive challenges they experience. We then explore the role of argumentation in science, review research on both experts' (scientists') and novices' (students') argument writing and highlight successful cognitive strategies for teaching argument writing with neurotypical learners. We further discuss SWDs' general writing challenges and how researchers have improved their abilities to comprehend and evaluate scientific information and improve their domain-general writing. Cognitive apprenticeships appear advantageous for teaching SWDs science content and how to write scientific arguments, as this form of instruction begins with problem solving tasks that connect literacy (e.g., reading, writing, argumentation discourse) with epistemic reasoning in a given domain. We illustrate the potential of such apprenticeships by analyzing the conceptual quality of arguments written by three SWDs who participated in a larger quantitative study in which they and others showed improvement in the structure of their arguments. We end with suggestions for further research to expand the use of cognitive apprenticeships.